2005
DOI: 10.1038/sj.ijo.0803158
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous administration of ghrelin stimulates energy intake in healthy lean human volunteers

Abstract: Background: The gastric hormone ghrelin appears a useful agent to stimulate food intake in people with anorexia of illness. The loss of ghrelin's acyl group renders it inactive, thus it has been thought that subcutaneous administration may be problematic. Objective: To investigate whether human subjects are sensitive to the effects of ghrelin administered by single subcutaneous injection. Study design: Randomized, double-blind, placebo-controlled trial. Subjects: Sixteen healthy lean volunteers (eight men and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
67
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(69 citation statements)
references
References 13 publications
1
67
0
1
Order By: Relevance
“…Unlike leptin, ghrelin, a 28-residue, post-translationally acylated, endogenous ligand of the GH secretagogue receptor (GHSR1a), is a predominantly stomach-derived, anabolic hormone whose circulating levels are homeostatically increased by energy insufficiency to signal the central nervous system. Given pharmacologically, the Ser 3 -n-octanoylated form of ghrelin is orexigenic and decreases energy expenditure and utilization of fat as an energy substrate, leading to weight gain and adiposity with chronic central administration (Druce et al, 2006;Tschop et al, 2000;Wortley et al, 2005). Because leptin and ghrelin respectively increased and decreased in chow/preferred-fed rats, obesity and feeding adaptations probably developed despite energy balance-appropriate, homeostatic accommodations to levels of both hormones (similar to diet-induced human obesity), rather than because of dysregulated release.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike leptin, ghrelin, a 28-residue, post-translationally acylated, endogenous ligand of the GH secretagogue receptor (GHSR1a), is a predominantly stomach-derived, anabolic hormone whose circulating levels are homeostatically increased by energy insufficiency to signal the central nervous system. Given pharmacologically, the Ser 3 -n-octanoylated form of ghrelin is orexigenic and decreases energy expenditure and utilization of fat as an energy substrate, leading to weight gain and adiposity with chronic central administration (Druce et al, 2006;Tschop et al, 2000;Wortley et al, 2005). Because leptin and ghrelin respectively increased and decreased in chow/preferred-fed rats, obesity and feeding adaptations probably developed despite energy balance-appropriate, homeostatic accommodations to levels of both hormones (similar to diet-induced human obesity), rather than because of dysregulated release.…”
Section: Discussionmentioning
confidence: 99%
“…For a review on this topic, we refer the reader to Skibicka and Dickson 2011. In normal weight healthy volunteers, ghrelin has been shown to increase hunger scores, to enhance food palatability and to increase caloric intake in a free-feeding buffet situation (Cummings et al 2004;Druce et al 2006;. One recent study of food economics reported that ghrelin even increases the amount of money an individual is prepared to pay for individual food items (Tang et al 2011).…”
Section: The Central Ghrelin Signalling System Is Required For Rewardmentioning
confidence: 99%
“…(Nagaya et al, 2001a;Wren et al, 2001;Akamizu et al, 2004;Schmid et al, 2005;Levin et al, 2006) or subcutaneous (Enomoto et al, 2003;Druce et al, 2006) ghrelin showed safety and tolerability at dosages up to 10 mg kg À1 -sufficient to promote orexigenic, prokinetic, and GH-releasing effects; in those studies, a sensation of warmth, sleepiness, bowel movements, and hunger were reported. Comparable results with i.v.…”
mentioning
confidence: 98%